2019
DOI: 10.3892/ol.2019.10185
|View full text |Cite
|
Sign up to set email alerts
|

Serum pyruvate dehydrogenase kinase as a prognostic marker for cholangiocarcinoma

Abstract: Pyruvate dehydrogenase kinase (PDK) is a Ser/Thr kinase that inactivates mitochondrial pyruvate dehydrogenase and serves a key role in aerobic glycolysis, which is a hallmark of cancer cells. The present study determined the PDK expression in cholangiocarcinoma (CCA) tissues and sera to evaluate their applicability as a biomarker for CCA. Using proteomic analysis, PDK was revealed to be the most overexpressed mitochondrial protein in CCA tissues. Then, the expression of PDK isoforms in CCA tissues was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Moreover, PDK3 expression levels were considerably higher in CCA sera compared with the benign biliary diseases and healthy groups. In agreement, PDK3 levels correlated with a short survival time in CCA [37]. Overall, these data suggest that inhibition of mitochondrial metabolism and hence the sustenance of the glycolytic flux can be fundamental in CCA growth.…”
Section: Tfr1 High Expressionsupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, PDK3 expression levels were considerably higher in CCA sera compared with the benign biliary diseases and healthy groups. In agreement, PDK3 levels correlated with a short survival time in CCA [37]. Overall, these data suggest that inhibition of mitochondrial metabolism and hence the sustenance of the glycolytic flux can be fundamental in CCA growth.…”
Section: Tfr1 High Expressionsupporting
confidence: 73%
“…Other studies support the up-regulation of Warburg metabolism in CCA: pyruvate dehydrogenase kinases (PDKs) are Ser/Thr kinases that phosphorylate/inactivate mitochondrial pyruvate dehydrogenase, thus decreasing the oxidation of pyruvate in the tricarboxylic acid (TCA) cycle and increasing the Warburg effect [70]. Sanmai S. et al, [37] demonstrated that PDK1, PDK2 and PDK3, were significantly overexpressed in 15 CCA tissues compare to normal ones. Moreover, PDK3 expression levels were considerably higher in CCA sera compared with the benign biliary diseases and healthy groups.…”
Section: Tfr1 High Expressionmentioning
confidence: 95%
See 1 more Smart Citation
“…Apart from AIFM3, several mitochondrial proteins such as mitochondrial ribosomal protein, mitochondrial stress 70 protein (mortalin), pyruvate dehydrogenase kinase 3, and manganese superoxide dismutase have been detected in the serum, and has been used as serum marker for breast cancer, colorectal cancer, CCA, and ovarian cancer [ 20 , 21 , 22 , 23 ] The present results suggest that AIFM3 should be added as a mitochondrial protein marker in the sera of patients with CCA and probably other cancers. In the present study, serum AIFM3 level in the CCA patients group was significantly ( p < 0.0001) higher than that of HC.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1α is an important enzyme for metabolic adjustment during hypoxia and is involved in cancer cell survival, angiogenesis, and metastasis (28,37,57). CCA patients showed a higher level of Pyruvate dehydrogenase kinase 1 (PDK1) (58), which has been known to control the metabolic shift during hypoxia via regulating the acetyl-coA production to yield energy in the TCA cycle by mitochondria oxidation (59,60). The mTOR pathway regulates energy homeostasis and engages in cancer cell survival in cellular metabolic stress such as depletion in nutrients and energy (23,24).…”
Section: Therapeutic Interventions Related To Reprogrammed Metabolismmentioning
confidence: 99%